Mitomycin-Induced Interstitial Pneumonitis in a Patient with BRCA2 Associated Metastatic Pancreatic Carcinoma - Saif, Muhammad Wasif; Dai, Tong (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: Space-filling model of the mitomycin molecule (Author: Jynto (talk); Wikimedia Commons)